Validation and factor analysis of the parental bonding instrument in Japanese pregnant women - Maya Sato (Nature Portfolio, 2021)
Abstract The Parental Bonding Instrument (PBI) evaluates parental attitudes derived from an individual’s childhood experiences with their parents. The factor structure of the PBI differs depending on variables such as psychosocial factors including culture, race, sex, and psychological and social conditions of participants. Although previous studies of the relationships between perinatal depression and parenting experiences have used the factor structures of the PBI from the general population, it is unclear whether the same factor structures are appropriate in the highly variable perinatal period. In this study, complete responses to the PBI and the Edinburgh Postnatal Depression Scale (EPDS) were received from 932 primiparas at 25 weeks of gestation and at 1 month postpartum. An exploratory factor analysis was performed on half of the responses, and it was confirmed that the three factors were care, interference, and autonomy. Confirmatory factor analysis of the remaining half of the answers showed comprehensible fitness. Each factor showed a high degree of internal consistency, and each factor of the PBI correlated with the EPDS, indicating construct validity. The reliability and validity of the PBI in perinatal Japanese women were confirmed, and it was found that the PBI had a three-factor structure.